Negative Skin Friction Tiang Pancang pada Tanah Lempung Studi Kasus Pabrik Tesktil, Bale Endah - Widjaja, Budijanto; Lestari, Anastasia Sri; Agusman, Agusman (Universitas Kristen Maranatha, 2006)
There were several geotechnical problems at the textile factory in Bale Endah. The main problem that arose at this factory was the settlement of the soft clay soil which resulted in deformation of the tiled floor and warping of the west wall of the factory as well as cracking and collapse of the culvert in the drainage system at the location of the center column of the factory. The soil stratification at this location was dominated by soft to stiff clay layers and a sand lens layer was also found at 9-12 m depth. Therefore, the relative subsidence was more determined by the consolidation settlement of the clay. In addition to the problem of clay settlement, another problem arises, namely the problem of negative skin friction on the pile foundation. This occurs because there is an embankment on top of the clay soil which results in additional load on the soil, so that the soil settlement becomes greater than the settlement of the pile foundation. The analysis showed that the total settlement of the clay consolidation was 35.60 cm within 12.00 years and the total settlement of the pile foundation with a column load of 16.72 tons was 10.44 cm. Due to negative blanket friction, the pile foundation used is not strong enough to withstand the working load. The location of the neutral point is at a depth of 23.25-28 m for a pile foundation length of 30 m deep.